Paths to viability: transnational strategies among Ghana's small-scale ICT entrepreneurs - Taylor, L (International Migration Institute, 2011)
This paper uses fuzzy-set qualitative comparative analysis (fsQCA) to investigate the relative importance of mobility in the formation and viability of the internet cafes that are responsible for most local internet access in poor countries. It is based on a study of Ghanaian commercial internet cafes, the majority located in the country’s remote northern regions, with a second group of cafes studied in the capital city, Accra. The findings presented here demonstrate that while international mobility is typically a strategy available to the better-off, it nevertheless benefits younger and less advantaged entrepreneurs disproportionately in terms of their return on investment. Furthermore, both migrant and non-migrant cafe owners in Ghana are using transfers from abroad of all kinds, especially physical capital and knowledge, to create and sustain their businesses. The study also shows that for those whose presence in the sector is marginal and precarious, i.e. the owners of the smallest businesses and the younger and poorer entrepreneurs, these transfers represent an essential strategy in maintaining a viable enterprise.